The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1038/sj.sc.3101481
|View full text |Cite
|
Sign up to set email alerts
|

Improved kinematics of unrestrained arm raising in C5–C6 tetraplegic subjects after deltoid-to-triceps transfer

Abstract: Study design: Prospective comparative study. Objective: To determine whether control of upper limb joint synergy during unrestrained arm raising involving shoulder and elbow flexion is modified by deltoid-to-triceps transfer. Setting: Rehabilitation unit for spinal cord injury patients, France. Methods: Five C6 subjects with C5-C6 tetraplegia sustained posterior deltoid-to-triceps transfer and were compared to a control group of 11 subjects. Kinematics of shoulder and elbow joints before, 6 month and 1 year af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
(49 reference statements)
0
25
0
1
Order By: Relevance
“…Generalised analysis across groups seems to mask the individuality of patients' responses and adaptation to surgery. As this study established the workspace in which tetraplegic patients can reach and the ability of tetraplegics to reach to this workspace, this study coupled with data from functional tasks 9 and movement control 6 has provided a greater understanding of the functional benefits of the tendon transfer. Future studies using EMG within the workspace would allow researchers to examine how the central nervous system adapts to the tendon transfer and activates the upper-limb muscles to reach effectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Generalised analysis across groups seems to mask the individuality of patients' responses and adaptation to surgery. As this study established the workspace in which tetraplegic patients can reach and the ability of tetraplegics to reach to this workspace, this study coupled with data from functional tasks 9 and movement control 6 has provided a greater understanding of the functional benefits of the tendon transfer. Future studies using EMG within the workspace would allow researchers to examine how the central nervous system adapts to the tendon transfer and activates the upper-limb muscles to reach effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Reaches at these heights should be considered when undertaking assessment of tetraplegic participants clinically or experimentally in the future. Remy-Neris et al 9 showed the improvement in co-ordination shown by post-tendon transfer tetraplegics during two arm raising tasks. After 16 months, the tetraplegic participants in their study had comparable range of motion and angular velocity to healthy control participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results corroborate clinical observations of the functional benefits of surgical restoration of active elbow extension by musculo-tendinous transfer. 8,13,24,30 Current hypotheses concerning the benefit of the presence of an active elbow extensor include the ability to maintain a stable arm posture, especially when the hand is raised above the shoulder level, as is the case in the present task, 31 the ability to interact with a variety of external objects and forces, 32 or the ability to propulse a manual wheelchair. In addition, our results suggest that the presence of a non-paralysed triceps, or of a surgically transferred muscle, facilitates prehension, probably by stabilisation of the elbow during the transport of the objects.…”
Section: Importance and Function Of An Active Elbow Extensormentioning
confidence: 99%